Win or lose. Physical and physiological responses in paddle tennis competition according to the game result - Roldán-Márquez, R.; Onetti-Onetti, W.; Alvero-Cruz, J. R.; Castillo-Rodríguez, A. (International Journal of Performance Analysis in Sport, 2022)
Sports success can be determined by technical level, physical condition, but also with behaviour and decision-making in competition. The main aim of this study was to compare the different physiological and physical responses of professional male paddle-tennis players as a function of the game result. Sixty sets and twenty-four players were analysed in the Spanish National Championships. Heart rate (HR), lactate concentrations, rating of perceived exertion (RPE), covered distance and speed and sprints were measured. Comparative tests were performed to compare winners and losers, and RPE was analysed using the Receiver Operating Characteristic (ROC) curve test through Logit model. Losers showed greater results in the mean HR (154.1±15.6 beats·min-1) than winners (144.2±19.1 beats·min-1, p<0.01). A score of 6-10 or 16-20 points in RPE, entailed a high or low probability of winning the set (72-92% or 6-23%, respectively). Physical responses were higher in losers, e.g. higher distances, mean velocity, sprints number between 2.1-9.0 km·h-1. As conclusions, players who finally lose the match demand greater physical and physiological responses in general. It is established, as in other racket sports, that the player`s position on the court is key to determining victory in this sport.